Flaxseed oil and prevention of pulmonary fibrosis - Choi, Seojin (Kansas State University, 2012)
Although omega-3 fatty acids have been a hot issue in nutrition for years, there remains a paucity of research on the topic of omega-3 fatty acid and pulmonary fibrosis and the mechanism is still unclear. The purpose of this research is to investigate the preventive effects of flaxseed oil for bleomycin-induced pulmonary fibrosis in rats and to find the possible underlying mechanisms. There are two experiments demonstrated in this dissertation, one is with various doses of flaxseed oil in the diet (0, 2.5, 5, 7.5, 10, 12.5, and 15 % (w/w)), and the other is with different times of sacrificing animals after oropharyngeal bleomycin treatment (days 7 and 21). In the first study, three proteins including transforming growth factor-[beta] (TGF-[beta]), interleukin-1 (IL-1), and [alpha]-smooth muscle actin ([alpha]-SMA), commonly associated with fibrotic inflammation in the lung, were examined by Western blot and fatty acids composition of the diets and tissues were analyzed by gas chromatography (GC). Fifteen percent of flaxseed oil group significantly reduced septal and vascular thickness and fibrosis in the lung, and significant cardiac fibrosis in the heart. The amount of IL-1 and [alpha]-SMA decreased significantly as the amount of omega-3 fatty acids increased, whereas TGF-[beta] did not change significantly. The next study further reported the time-course effect and potential underlying mechanisms. Both interleukin-6 (IL-6), a protein associated with fibrotic inflammation in the lung, and renin, an enzyme related to renin-angiotensin system, were examined by Western blot. The time-dependent increase of IL-6 in response to bleomycin treatment was reversed by flaxseed oil diet. Although renin was not significantly different in the kidney, it suggested that the renin-angiotensin system may be involved locally. In addition, the profiles of fatty acids in both liver and kidney tissues as measured by lipidomics demonstrated a significant increase of omega-3: omega-6 ratio in the flaxseed oil-fed groups. Overall, these results indicated for the first time that the omega-3 fatty acids rich in flaxseed oil inhibited the formation of pulmonary fibrosis in a dose-dependent manner - however the moderate dose of flaxseed oil was most effective - via anti-inflammatory mechanisms, which appears associated with the modulated fatty acid composition in the tissues.
Keywords: Short chain omega-3 fatty acid; Prevention of pulmonary fibrosis; Bleomycin; Flaxseed oil; Idiopathic pulmonary fibrosis; Nutrition (0570)